Multimodality in liquid biopsy: does a combination uncover insights undetectable in individual blood analytes? - Keup Corinna; Kimmig Rainer; Kasimir-Bauer Sabine (Journal of Laboratory Medicine, 2022)
The heterogeneity of each individual oncologic disease can be mirrored by molecular analysis of a simple blood draw in real time. Liquid biopsy testing has been shown useable for cancer detection, proof of minimal residual disease, therapy decision making and monitoring. However, an individual blood analyte does not present a comprehensive picture of the disease. It was recently shown that multi-modal/multi-parametric/multi-analyte liquid biopsy testing has the advantage of generating a high-resolution snapshot of the disease complexity. The different blood analytes such as circulating tumor cells, circulating immune cells, tumor-educated platelets, extracellular vesicles, cell-free DNA, cell-free RNA and circulating proteins complement each other and have additive value for clinical cancer management. We, here, like to review the studies leading to these promising conclusions and like to, at the end, mention that many challenges lie ahead before the translation into the clinic can be accomplished, including issues concerning clinical utility, method standardization, cost reimbursement and data management.